Fluorescent Amplified Fragment Length Polymorphism Genotyping of Campylobacter jejuni and Campylobacter coli Strains and Its Relationship with Host Specificity, Serotyping, and Phage Typing - Hopkins, Katie L. (American Society for Microbiology (ASM), 2004)
Fluorescent amplified fragment length polymorphism (FAFLP) analysis was applied to 276 Campylobacter jejuni strains and 87 Campylobacter coli strains isolated from humans, pigs, cattle, poultry, and retail meats to investigate whether certain FAFLP genotypes of C. jejuni and C. coli are associated with a particular host and to determine the degree of association between FAFLP-defined genotypes and heat-stable serotypes and/or phage types. Within C. coli, the poultry strains clustered separately from those of porcine origin. In contrast, no evidence of host specificity was detected among C. jejuni strains. While C. coli strains show host specificity by FAFLP genotyping, C. jejuni strains that are genotypically similar appear to colonize a range of hosts, rather than being host adapted. Some serotypes and/or phage types (C. jejuni serotype HS18, phage type PT6, and serophage type HS19/PT2 and C. coli HS66, PT2, and HS56/PT2) were the most homogeneous by FAFLP genotyping, while others were more heterogeneous (C. jejuni HS5 and PT39, and C. coli HS24 and PT44) and therefore poor indicators of genetic relatedness between strains. The lack of host specificity in C. jejuni suggests that tracing the source of infection during epidemiological investigations will continue to be difficult. The lack of congruence between some serotypes and/or phage types and FAFLP genotype underlines the need for phenotypic testing to be supplemented by genotyping. This study also demonstrates how, in general, FAFLP generates “anonymous” genetic markers for strain characterization and epidemiological investigation of Campylobacter in the food chain.